Potentially traumatic events, coping strategies and associations with mental health and well-being measures among conflict-affected youth in Eastern Democratic Republic of Congo. Issue 1 (December 2016) - Cherewick, Megan; Doocy, Shannon; Tol, Wietse; Burnham, Gilbert; Glass, Nancy
Abstract Background Youth in conflict and post-conflict settings are exposed to a variety of potentially-traumatic events that impact their mental health and well-being. The purposes of this study were to examine coping strategies among conflict-affected youth exposed to potentially-traumatic events and the relationship to psychological symptoms and well-being in the Democratic Republic of Congo (DRC). Methods A total of 434 male and female youth (ages 10–15 years) completed data collection with a trained Congolese interviewer. The survey instrument included measures of exposure to potentially traumatic events, an adapted coping strategies checklist, and measures of psychosocial distress and well-being. Exploratory factor analyses was used to identify coping strategies and Hierarchical regression was used to assess how coping strategies were associated with psychological symptoms including internalizing and externalizing problems and well-being outcomes including prosocial behavior and self-esteem. Results Exploratory Factor analysis suggested four coping strategies; problem-focused, emotion-focused, avoidance and faith-based strategies. Problem-focused coping strategies were associated with greater internalizing and externalizing problems and lower prosocial behavior in both boys and girls. However, when problem-focused strategies were used with emotion-focused coping strategies, the result was fewer internalizing problems in girls and fewer externalizing problems in boys and girls. Emotion-focused, avoidance and faith based strategies were associated with better self-esteem. Conclusion These results suggest a complex relationship between coping strategies, psychological symptoms and well-being and contradict evidence that problem-focused strategies benefit mental health while emotion-focused strategies harm mental health, particularly in conflict and post-conflict settings. The results suggest coping flexibility, or use of multiple coping strategies may be particularly useful to improving mental health and well-being. The need for context specific understandings of coping strategies in conflict-affected populations is highlighted by the results of the study.